A size-based ecosystem model - Lars J. Ravn-Jonsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
Ecosystem Management requires models that can link the ecosystem level to the operation level. This link can be created by an ecosystem production model. Because the function of the individual fish in the marine ecosystem, seen in trophic context, is closely related to its size, the model groups fish according to size. The model summarises individual predation events into ecosystem level properties, and thereby uses the law of conservation of mass as a framework. This paper provides the background, the conceptual model, basic assumptions, integration of fishing activities, mathematical completion, and a numeric implementation. Using two experiments, the model's ability to act as tool for economic production analysis and regulation design testing is demonstrated. The presented model is the simplest possible and is built on the principles of (i) size, as the attribute that determines the predator-prey interaction, (ii) mass balance in the predator-prey allocation, and (iii) mortality and somatic growth as a consequence of the predator-prey allocation. By incorporating additional assumptions, the model can be extended to other dimensions of the ecosystem, for example, space or species. The formulation and description of the present model can serve as a reference for future work.
Keywords: 330; ecosystem-model; side-based-model; trophic-model; numeric; fishery; economic.; Umweltökonomik; Meeresnutzung; Fischerei; Theorie